A viscoelastic cohesive/friction coupled model for delamination analysis of composite laminates. (October 2019) - Liu, P.F.; Peng, X.Q.; Guo, Z.Y.
Highlights: A viscoelastic cohesive model using Schapery-type theory is developed. Recursive algorithm is developed to solve the viscoelastic cohesive model. A viscoelastic cohesive/frictional contact coupled model is developed. Numerical algorithm is developed to solve the viscoelastic cohesive/friction coupled model. Explicit FEA is adopted to solve the developed model. Abstract: This paper develops a viscoelastic cohesive/frictional contact coupled model for delamination analysis of composite laminates. First, a viscoelastic cohesive model is developed, in which the regular cohesive tractions are expressed as the modified Xu and Needleman's exponential traction-separation function and the viscous cohesive tractions are described by the Schapery-type hereditary integral function. The Prony series is used to expand the dimensionless cohesive stiffness. The recursive algorithm is employed to solve the viscous cohesive traction. Second, the regular tangential cohesive traction is further coupled with the frictional stress to deal with the contact problem, where the cohesive/frictional contact coupled algorithm is also developed. Third, the explicit finite element formulation is presented to solve the cohesive traction for finite-thickness interface. Finally, numerical results in terms of the single-leg bending (SLB) composite specimens with frictionless mixed-mode delamination and the end notched flexure (ENF) composite specimens with frictional shear delamination under low strain rate loading are used to validate the developed model by studying the effects of the cohesive strength, friction, load rate and mesh sizes on the load responses and the delamination growth behaviors.